Isolation and identification of fungi associated with Esca in Vinho Verde region (RDVV): northwest Portugal - Felgueiras, Mafalda (2008)
In the Portuguese Vinho Verde region (RDVV), during the last years the esca incidence is taking serious proportions. In this context, in the summers of 2004 and 2005 three vineyards were selected (two within the Monção subregion and one outside) in order to isolate associated Esca-fungi. Cordons were taken from 10 infected Alvarinho cultivar grapevines showing esca foliar symptomatology. Results confirm the occurrence of species P. chlamydospora and P. angustius in RDVV. They identify for the first time the species P. viticola and P. inflatipes, both is this wine region and in the Alvarinho grape variety. Results show that there are different strains within one fungus specie in the majority of the isolated species, and also that the closer the vineyards, the higher the similarity of the fungi strains.